CLIMATE AND VEGETATION CHANGES 180,000 TO 345,000 YEARS AGO RECORDED IN A DEEP-SEA CORE OFF PORTUGAL - Roucoux K.H.; Tzedakis P.C.; de Abreu L.; Shackleton N.J. (My University, 2006)
A new high-resolution combined marine proxy-pollen sequence from the Portuguese margin, MD01-2443, enables direct comparison of ocean and ice volume changes with vegetation development in south-west Iberia during marine isotope stages (MIS) 7, 8 and 9. Changes in sea surface conditions on both orbital and millennial time scales are closely mirrored by forest extent, indicating a coherence of climate variability between the North Atlantic and south-west Iberia. Deglacial warming at the start of MIS 7 and 9 was interrupted by incursions of subpolar water masses at the site, accompanied by reversals in tree population expansion. During MIS 7e and 9e, the close relationship in timing and amplitude between vegetation and offshore conditions broke down: early forest collapse points to pronounced cooling and aridification on land which, although not accompanied by a change in water masses at the Portuguese margin, appears to have coincided with abrupt decreases in atmospheric methane concentration recorded in Antarctic ice cores. The most extreme glacial conditions of MIS 8 occurred during the early part, followed by an interval of warmer conditions and tree population expansion ~ 263 ka. This has sometimes been considered as indicating an early deglaciation, but the data presented here show that it was distinct from Termination III, which occurred later, in line with Milankovitch forcing. A sub-orbital oscillation in both isotopic and pollen records is observed at the end of MIS 7 (ca. 184 ka) which appears to be coeval with a recently identified sea level high stand. © 2006 Elsevier B.V. All rights reserved.
Keywords: LAND-OCEAN CORRELATION; MARINE PALYNOLOGY; MIS 7; MIS 8; MIS 9; NORTH ATLANTIC; PORTUGAL